2012
DOI: 10.1039/c2cc31414b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolysis of lignosulfonate into phenols over heterogeneous nickel catalysts

Abstract: We report a strategy for the catalytic conversion of lignosulfonate into phenols over heterogeneous nickel catalysts. Aryl-alkyl bonds (C-O-C) and hydroxyl groups (-OH) are hydrogenated to phenols and alkanes, respectively, without disturbing the arenes. The catalyst is based on a naturally abundant element, and is recyclable and reusable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
148
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(155 citation statements)
references
References 24 publications
2
148
3
2
Order By: Relevance
“…While nickel is able to cleavage C-O aliphatic bonds, it is less active for the rupture of aromatic C-O and arene bonds. Lignin conversion to alkane-substituted guaiacols over Ni catalysts is independent of the support type (e.g., activated carbon, zeolite, or MgO) [25]. Higher conversions were obtained in the presence of diol or triol functions, such us glycerol and ethylene glycol.…”
Section: Hydrogenolysismentioning
confidence: 78%
See 2 more Smart Citations
“…While nickel is able to cleavage C-O aliphatic bonds, it is less active for the rupture of aromatic C-O and arene bonds. Lignin conversion to alkane-substituted guaiacols over Ni catalysts is independent of the support type (e.g., activated carbon, zeolite, or MgO) [25]. Higher conversions were obtained in the presence of diol or triol functions, such us glycerol and ethylene glycol.…”
Section: Hydrogenolysismentioning
confidence: 78%
“…Higher conversions were obtained in the presence of diol or triol functions, such us glycerol and ethylene glycol. Song and co-workers concluded that for lignosulfates, Ni(0) active sites catalyse hydrogenolysis of C-O-C bonds, C-OH bonds in side alkyl chains, and the reduction of sulfonate groups into hydrogen sulfide (H 2 S) [25]. He et al [26] studied the cleavage of aromatic ether linkages by a nickel catalyst in model lignin compounds, such as benzyl phenyl ether, 2-phenylethyl phenyl ether, and diphenyl ether, which contain b-O-4, a-O-4, and 4-O-5 bonds, respectively.…”
Section: Hydrogenolysismentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 We recently reported a strategy of catalytic conversion of lignosulfonate into 4-ethylguaiacol and 4-propylguaiacol over heterogeneous nickel catalysts. 43 Our study reveals that aryl-O-alkyl bonds (C-O-C) and hydroxyl groups of lignin are hydrogenated to phenols and alkanes, respectively, while preserving the aromatic structure.…”
Section: Introductionmentioning
confidence: 99%
“…On the assumption that the UV absorption of phenylpropanoid in lignin and guaiacol approximately equals each other, the dissolved lignin was calculated based on a guaiacol standard curve used in our previous study. 43 …”
Section: Measurement Of Lignin Solubility In Various Solventsmentioning
confidence: 99%